Deeper-Layer Body Tissue Temperature Control Using Multi-sensory Transducer - Dumciene, Audrone; Sipaviciene, Saule (Elektronika ir Elektrotechnika, 2015)
For the monitoring of deeper layers of human tissue temperature during cooling the four-thermistor transducer was proposed. The Steinhart-Hart equation was used to linearize the temperature-resistance characteristics of thermistors. Transducer structure and temperature fields in the tissues of the body were simulated using COMSOL Multiphysics. The ratio of transducer’s equivalent thermal resistances was determined using numerical and physical experiments. The difference of values of the temperature measured at a depth of 30 mm in tissue by invasive and non-invasive method was less than ± 0.5 °C. DOI: http://dx.doi.org/10.5755/j01.eee.21.5.13320